About Methodology and Methods of Language Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
As the history of linguistics testifies, in each period and in each region, the methods of language research can be chosen differently, determined differently depending on the purpose of the research. Naturally, this is primarily due to the approach to language. In Ancient Greece, language was considered as an element of philosophy, and its study was also conducted from the point of view of philosophical and logical laws. In ancient India, Arabia, and Central Asia, it was approached from the perspective of practical educational needs. In ancient times, when determining the material of language, its units and the laws of functioning, they were compared with each other, comparing and contrasting, existing similarities and dissimilarities were identified. In ancient times, work was carried out based on such methods. Methods of scientific language research.